Uporaba prostorskih ključev pri učencih osmega razreda osnovne šole - Lapuh, Barbara; Selan, Jurij (Revija za elementarno izobraževanje, 2018)
The Usage of Visual Gradients at Eighth-graders. In the article, we address an issue that can be observed in art lessons in the eighth and ninth grades of primary school in Slovenia. This issue is related to the ability to articulate the illusion of space in drawing by the use of visual gradients. Experience has shown that even though pupils have acquired knowledge of visual gradients, they fail to apply this knowledge in subsequent similar drawing tasks. Therefore, we performed a qualitative research study during art lessons in which we sought to analyse how eighth-graders (a sample of 28 pupils), once given the knowledge of visual gradients, use this knowledge in subsequent drawing assignments in which there is no explicit demand for the use of visual gradients. One of the key findings based on the results is that two-thirds of pupils did not apply theirknowledge of visual gradients in the second drawing (despite showing it in first drawing). This reveals to us that a single exposure to visual gradients does not lead pupils to internalise the knowledge of visual gradients or to use it spontaneouslyDOI: 10.18690/rei.11.2.121-141.2018COBISS-ID: 12043849
Keywords: visual gradients; illusion of space; art lessons